Analysis of electro-optical and dielectric parameters of TiO2 nanoparticles dispersed nematic liquid crystal. Issue 2 (3rd April 2018) - Katiyar, Rohit; Pathak, Govind; Srivastava, Atul; Herman, Jakub; Manohar, Rajiv
ABSTRACT: The present investigation is focused on to find out the role of TiO2 nanoparticles (NPs) on altering the dielectric and electro-optical parameters of nematic liquid crystal (NLC). In addition to this, we also optimized the concentration of dopant (0.25 wt%) for a saturation value of permittivity and dielectric anisotropy in the doped system. Dielectric spectroscopy has been performed with the variation of frequency and temperature to investigate the various dielectric parameters, which demonstrate that the investigated NLC is of positive dielectric anisotropy; the observed result shows a decrement in the value of relative permittivity and dielectric anisotropy; however, the permittivity value increases for higher concentration of dopant but remains less than that of pure NLC. Electro-optical measurements have also been performed to compute the optical response of pure and dispersed NLC. It is found that optical response decreases for the NP-doped systems. This optimized concentration of NPs in NLC matrix can have various credential applications in the field of active matrix display and holography.